Chance and determinism in Avicenna and Averroes - Belo, Catarina C. M. de M. 1974- (Islamic philosophy, theology and science, 2007)
This book examines the question whether medieval Muslim philosophers Avicenna (Arabic Ibn Sīnā 980-1037) and Averroes (Arabic Ibn Rushd 1126-1198) are determinists. With a focus on physics and metaphysics it studies their views on chance events in nature, as well as matter, in particular prime matter, and divine providence. In addition it sets their positions against the historical/philosophical background that influenced their response, the Greco-Arabic philosophical tradition - Aristotelian and Neoplatonic - on the one hand, and the tradition of Islamic theology ( kalām ) on the other. In comparing their philosophical systems, it lays emphasis on the way in which Avicenna and Averroes use these traditions to offer an original answer to the problem of determinism.